Further Liberalization and Promotion of Private Entrepreneurship in Uzbekistan - Sadullayev Murodulla Lutfullayevich; Rahmov Muhammadjon Muzaffarovich (Periodica Journal, 2022)
Operates in different directions throughout human life. Among them, entrepreneurial activity is of special importance. Today, the attention to entrepreneurship in our country is growing. In this article, we talk about starting an entrepreneurship in Uzbekistan, the opportunities, problems and solutions.
Keywords: opportunities; problems; solutions; different